Clinical Implications and Translation of an Off-Target Pharmacology Profiling Hit: Adenosine Uptake Inhibition In Vitro - Hamid R. Amouzadeh (Translational Oncology, 2019)
Off-target activities of drug candidates observed during in vitro pharmacological profiling frequently do not translate to adverse events (AEs) in human. This could be because off-target activities do not have functional consequences, are not observed at exposures achieved during clinical testing, or may not translate into clinical outcomes. We report clinical consequences of an off-target activity observed during profiling of AMG 337, a selective inhibitor of the mesenchymal-epithelial transition factor being evaluated for treatment of solid tumors. In our screen of 151 potential off-targets, AMG 337 inhibited only adenosine transporter (AT). During clinical trials, headache emerged as the dose-limiting AE in the first-in-human trial. It was thought that headache was caused by extracellular accumulation of adenosine from inhibition of AT by AMG 337 and subsequent adenosine-mediated vasodilation through adenosine receptors (ARs). Further nonclinical studies were performed to evaluate this hypothesis. AMG 337 inhibited AT function in dog and human cells in vitro and dog and human arteries ex vivo. In a dog telemetry study, AMG 337 caused hypotension, which was reduced by pretreatment with theophylline, an AR antagonist. Overall, nonclinical and clinical data suggested that headache was due to cerebral vasorelaxation caused by AMG 337-mediated inhibition of AT. When subjects were advised to drink coffee, an AR antagonist, prior to AMG 337, the severity of headaches was reduced, allowing them to continue treatment. These findings demonstrate the importance of carefully evaluating clinical observations during early drug development and the value of translational nonclinical studies to investigate the mechanism of action driving clinical observations.